Phylogenetic and environmental DNA insights into emerging aquatic parasites: implications for risk management. Issue 6 (May 2018) - Sana, Salma; Williams, Chris; Hardouin, Emilie A.; Blake, Adrian; Davison, Phil; Pegg, Josie; Paley, Richard; Zhang, Tiantian; Andreou, Demetra
Graphical abstract: Highlights: Sphaerothecum destruens has spread to Europe through the translocation of its reservoir host, Pseudorasbora parva. Specific Pseudorasbora parva haplotypes have been linked with the presence of Sphaerothecum destruens. Parasite transfer to native communities has occurred through free living life stages of Sphaerothecum destruens. Abstract: Species translocation leads to disease emergence in native species of considerable economic importance. Generalist parasites are more likely to be transported, become established and infect new hosts, thus their risk needs to be evaluated. Freshwater systems are particularly at risk from parasite introductions due to the frequency of fish movements, lack of international legislative controls for non-listed pathogens and inherent difficulties with monitoring disease introductions in wild fish populations. Here we used one of the world's most invasive freshwater fish, the topmouth gudgeon, Pseudorasbora parva, to demonstrate the risk posed by an emergent generalist parasite, Sphaerothecum destruens . Pseudorasbora parva has spread to 32 countries from its native range in China through the aquaculture trade and has introduced S. destruens to at least five of these. We systematically investigated the spread of S. destruens through Great Britain and its establishment in native fish communities through a combination of phylogenetic studies of the host and parasite and a novel environmental DNA detection assay. Molecular approaches confirmed that S. destruens is present in 50% of the P. parva communities tested and was also detected in resident native fish communities but in the absence of notable histopathological changes. We identified specific P. parva haplotypes associated with S. destruens and evaluated the risk of disease emergence from this cryptic fish parasite. We provide a framework that can be applied to any aquatic pathogen to enhance detection and help mitigate future disease risks in wild fish populations.